Development of hybrid/active/passive silicon photonics for future technologies - Sia, Brian Jia Xu (Nanyang Technological University, 2021)
As a corollary of silicon manufacturing, silicon photonics has emerged as a viable photonic platform that has attracted the attention of many. The commercialization efforts of this technology, however, have remain somewhat limited due to several obstacles, technical and cost-related. As silicon is a poor emitter of light, the realization of an electrically-pumped monolithic laser source is unlikely. However, one may argue that the above have been satisfactorily resolved with the hybrid/heterogenous Ⅲ-Ⅴ/silicon photonic platform. In fact, the poor electro-optic conversion of silicon is one of the main factor that enables high performance hybrid/heterogenous Ⅲ-Ⅴ/silicon photonic laser diodes, resulting in significant improvement in performance over its Ⅲ-Ⅴ counterparts. While silicon photonics promises low cost, the premise is that the economies of silicon manufacturing is exploited. The inception of silicon photonics is mainly driven by the “interconnect bottleneck” in telecom and datacom. The data center transceiver market is attractive. However, there is a lack of a singular solution to all requirements in terms of reach, multisource agreement and standards. This implies that the cost of developing silicon photonics technology will be high unless the optical industry makes a concerted effort for standardization. As of now, the volumes required by silicon photonics are too low to draw commitment from large chip-making foundries. This work posits that for silicon photonics to be commercially viable, its range of applications must be widespread. The greater the adoption of silicon photonics in industry, the lower its cost. The condition is that firms must make the first step towards choosing silicon photonics for their applications. This work focuses on the development of silicon photonics technology beyond the traditional O and C bands. As a proof of concept to the broadband properties of the silicon-on-insulator platform, a high-performance arbitrary power splitter is realized at the longer transparency edge. In regard to the 2 μm waveband, which has been touted as a potential window for optical communications, the active Si-SiN multilayer platform, silicon switching as well as hybrid Ⅲ- Ⅴ/silicon photonic tunable lasers operating from 1881-1947, 1955-1992 nm has been demonstrated for the first time. In addition, at the application-rich wavelength region near 1.65 µm, a sub-kHz linewidth, hybrid Ⅲ-Ⅴ/silicon photonic tunable laser with a range of 1647-1690 nm is reported.